Bounds of their habitation: race and religion in American history - Harvey, Paul (American ways, 2017)
Introduction: religion and race in American history -- Red, white, and black in colonial American religion -- Religious freedom and religious intolerance in the early United States -- Religious ways of knowing race in antebellum America -- Religion, race, and the reconstruction of citizenship -- Religion, race, and immigration -- Religion and civil rights: the color of power -- Liberation theologies in a conservative age -- Epilogue